Proceedings of the 3rd Pan American Materials Congress - Meyers, Marc André; Benavides, Hector Alfredo Calderon; Brühl, Sonia P.; Colorado, Henry A.; Dalgaard, Elvi; Elias, Carlos Nelson; Figueiredo, Roberto B.; Garcia-Rincon, Omar; Kawasaki, Megumi; Langdon, Terence G.; Mangalaraja, R.V; Marroquin, Mery Cecilia Gomez; et al. (The Minerals, Metals & Materials Series, 2017)
This collection covers a variety of materials science topics and has contributions from leading scientists and engineers representing 8 countries and 9 international materials, metals, and minerals societies. Papers are organized into the following sections: Advanced Biomaterials Advanced Manufacturing Materials for Green Energy Materials for Infrastructure Materials for the Oil and Gas Industry Materials for Transportation and Lightweighting Minerals Extraction and Processing Nanocrystalline and Ultra-fine Grain Materials and Bulk Metallic Glasses Steels.